PAIN SYNDROME IN PATIENTS WITH BACK PAIN IN WOMEN - Muso B. Urinov; Mehriddin M. Usmonov (International Scientific and Current Research Conferences, 2023)
To determine the features of pain syndrome in patients with pain in the lower back in female patients.